The Gut-Brain Dopamine Axis: A Regulatory System for Caloric Intake - de Araujo, Ivan E (2012)
Post-ingestive factors are known to strongly modulate feeding behavior by providing feedback signals to the central nervous system on the current physiological state of the organism. Of particular interest is the identification of the physiological pathways that permit the brain to sense post-ingestive signals. We will review recent evidence supporting the concept that direct stimulation of the gastrointestinal tract with nutrients induces release of the catecholamine neurotransmitter dopamine. In addition, changes in dopamine efflux produced by direct stimulation of the gastrointestinal tract were found to reflect the caloric load of the infusates, suggesting that dopamine signaling may function as a central caloric sensor that mediates adjustments in intake according to the caloric density of a meal. Consistent with the above, blockade of dopamine signaling disrupts flavor-nutrient associations and impair the regulatory capacity to maintain constant caloric intake during intra-gastric feeding. Future research must determine the exact pathways linking gut nutrient administration to dopamine efflux. Current evidence points to parallel contributions by pre- and post-absorptive pathways, indicating that dopamine systems constitute a site of convergence through which distinct physiological signals can exert control over ingestive behaviors.